A distributed-consensus mechanism of decision making explains economically irrational behaviours. (July 2019) - Castellano, Sergio
Abstract : In humans, as in many other animals, preferences between options can be reversed when other irrelevant options are added to the choice set. Heuristics theories view such puzzling departure from economic rationality as evidence that decisions rely on simple rules that make a context-dependent use of the available information. The computational mechanisms underlying these rules, however, remain largely unresolved. Using a sequential sampling model of decision making, I show that irrational decisions may arise when an information processing mechanism that works optimally in one-choice tasks is co-opted in multiple-choice contexts. The model supports the assumption that different heuristics may sometimes be the elusive expression of a single general mechanism and that natural selection, rather than promoting the evolution of different mechanisms and rules, may favour the parsimonious use of bounded computational resources. Highlights: A 2-dimensional race model for sequential and simultaneous choice is presented. In sequential choices, the model is computationally optimal. In simultaneous choices, it is suboptimal and responsible for irrational decisions. Irrational decisions results from co-opting effective mechanisms in new contexts.